Proteins as Macromolecular Ligands for Metal‐Catalysed Asymmetric Transfer Hydrogenation of Ketones in Aqueous Medium. Issue 12 (25th March 2018) - de Jesús Cázares‐Marinero, José; Przybylski, Cédric; Salmain, Michèle
Abstract : Biohybrid catalysts resulting from the dative anchoring of half‐sandwich organometallic complexes [M(arene)(H2 O) x (Cl) y ] n + (M = Ru II, arene = η 6 ‐benzene, p ‐cymene or mesitylene; M = Ir III, Rh III, arene = η 5 ‐Cp*; x = 1–3, y = 0–2, n = 0–2) to bovine beta‐lactoglobulin (βLG) or hen egg white lysozyme showed unprecedented behaviour. These constructs were shown to catalyse the asymmetric transfer hydrogenation of aryl ketones in water with sodium formate as hydrogen donor at a much faster rate than the complexes alone. Full conversion of the benchmark substrate 2, 2, 2‐trifluoroacetophenone was reached with an ee of 86 % for the most selective biohybrid. Surprisingly, even the crude biohybrid gave a good ee despite the presence of non‐protein‐bound metal species in the reaction medium. Other aryl ketones were reduced in the same way, and the highest ee was obtained for ortho ‐substituted acetophenone derivatives. Furthermore, treatment of βLG with dimethyl pyrocarbonate resulted in a noticeable decrease of the activity and selectivity of the biohybrid, indicating that the sole accessible histidine residue (His146) was probably involved in the coordination and activation of Ru(benzene). This work underscores that protein scaffolds are efficient chiral ligands for asymmetric catalysis. The use of sodium formate instead of dihydrogen makes this approach safe, inexpensive and environmentally friendly. Abstract : Dative assembly of half‐sandwich ruthenium, rhodium or iridium complexes to beta‐lactoglobulin or lysozyme gave biohybrids that catalysed the asymmetric transfer hydrogenation of ketones with up to 86 % ee . Complementary investigations indicated involvement of His146 of beta‐lactoglobulin in ruthenium coordination.